노인 암 경험자의 우울 변화 궤적과 예측요인: 고령화연구패널조사(KLoSA)를 이용하여 - 현재원(Hyun, Jae Won); 김예솔(Kim, Yesol); 최모나(Choi, Mona) (Asian oncology nursing, 2021)
Purpose: The purpose of this study was to identify the trajectories of depressive symptoms and the predictive factors that determine the trajectories among elderly cancer survivors in South Korea. Methods: This study was a secondary data analysis using the Korean Longitudinal Study of Ageing (KLoSA). The inclusion criteria were adults who were aged 65 years or older, diagnosed with cancer, and participated in the panel survey at least three times. Data were analyzed using SPSS 25.0 and STATA 16.0 for Group-Based Trajectory Model. Results: This study comprised 197 participants. Depression trajectories were derived into the three groups of ‘nondepression,’ ‘mild depression,’ and ‘depression.’ As a result of multinomial logit analysis using ‘mild depression’ as a reference group, the significant predictors that differentiated the ‘non-depression’ and ‘mild depression’ groups was whether the subject was living alone or not (p=.001). Conclusion: To prevent and manage depression among the elderly cancer survivors living alone, it is necessary to first identify the social support resources from a cancer diagnosis. In addition, a social foundation should be established to enable elderly cancer survivors to utilize the supporting resources. Further studies should be conducted considering disease-specific variables such as types of cancers, stages of cancer, and treatment methods. KCI Citation Count: 0